2022
DOI: 10.1111/mms.12919
|View full text |Cite
|
Sign up to set email alerts
|

Variation in body mass and food intake of northern fur seals (Callorhinus ursinus)

Abstract: Estimates of prey and energy consumption are important for effective management and conservation of marine mammals and the ecosystems they inhabit. We used routinely collected husbandry data on body mass, food intake (kilograms), and energy intake (megajoules) from northern fur seals (Callorhinus ursinus) in zoological institutions to examine how these variables changed throughout the year, and with age, sex, and reproduction. Fur seals exhibited seasonal changes in all three variables, but the magnitude and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In one of the few studies on the cost of pregnancy in free-ranging marine mammals, Shero et al (2018) documented an increase in diving effort by pregnant Weddell seals (Leptonychotes weddelli) compared with nonreproductive females, particularly during the last trimester, which was attributed to an increase in gestational energy demand. There are fairly consistent observations across species that food intake decreases in the days to weeks leading up to birth, regardless of whether it fluctuates at other time periods (Ronald and Thomson, 1981;Joseph et al, 1987;Kastelein et al, 1990Kastelein et al, , 2000bRobeck et al, 2005;McHuron et al, 2022b). For some species, increases in food intake may not be related to the costs of gestation but rather due to an increase energy storage during gestation for the subsequent lactation interval (Noren et al, 2014).…”
Section: Maternal Food Intake During Gestation and Lactationmentioning
confidence: 94%
See 3 more Smart Citations
“…In one of the few studies on the cost of pregnancy in free-ranging marine mammals, Shero et al (2018) documented an increase in diving effort by pregnant Weddell seals (Leptonychotes weddelli) compared with nonreproductive females, particularly during the last trimester, which was attributed to an increase in gestational energy demand. There are fairly consistent observations across species that food intake decreases in the days to weeks leading up to birth, regardless of whether it fluctuates at other time periods (Ronald and Thomson, 1981;Joseph et al, 1987;Kastelein et al, 1990Kastelein et al, , 2000bRobeck et al, 2005;McHuron et al, 2022b). For some species, increases in food intake may not be related to the costs of gestation but rather due to an increase energy storage during gestation for the subsequent lactation interval (Noren et al, 2014).…”
Section: Maternal Food Intake During Gestation and Lactationmentioning
confidence: 94%
“…Changes in food intake of gestating marine mammals in human care are inconsistent, with conclusions typically drawn from a small number of individuals across only part of gestation. Some studies report no change or even decreases in food intake (in kg prey) during gestation (Joseph et al, 1987;Cheal and Gales, 1991;Kastelein et al, 1993Kastelein et al, , 2002Kastelein et al, , 2003, while others report increases, particularly later in gestation (Asper et al, 1988;Kastelein et al, 1990;Reddy et al, 1993;Kastelein et al, 2000a;McHuron et al, 2022b). There have also been conflicting findings within a species, such as for killer whales where Kastelein et al (2003) and Williams et al (2011) found no change in food intake while Asper et al (1988) documented increases beginning in the 13th month of gestation.…”
Section: Maternal Food Intake During Gestation and Lactationmentioning
confidence: 99%
See 2 more Smart Citations
“…heart rate, respiration rate, caloric intake) or behavioral (e.g. swim speed, measures of body movement or acceleration) characteristics ( Williams et al, 1993 ; Boyd et al, 1999 ; Butler et al, 2004 ; Fahlman et al, 2008 ; Young et al, 2011 ; Dalton et al, 2014 ; Noren et al, 2014 ; Kastelein et al, 2018 ; McHuron et al, 2022 ). Unfortunately, there are inherent inaccuracies when using such proxies due to unvalidated or weak relationships and substantial variation between individuals (McPhee et al 2003).…”
Section: Methods For Estimating Metabolic Ratementioning
confidence: 99%